Karakterisasi Senyawa Aktif Ekstrak Daun Buas-buas (Premna serratifolia) sebagai Anti Kanker Kolon pada Sel WiDr - Hadiarti, Dini; Mukhlishin, Hamdil (Jurnal Tumbuhan Obat Indonesia, 2025)
The leaves of Buas-buas or Premna serratifolia (P. serratifolia) have been used in Asian countries to treat inflammation, respiratory disorders, and postnatal recovery. Previous studies have demonstrated its anticancer activity against HT-29 and DLD-1 colon cancer cell lines; however, the isolation approach was selective and did not detect the range of active compounds or their functional groups. This study aims to identify functional groups and active compounds using Ultra High Performance Liquid Chromatography–High Resolution Mass Spectrometry (UHPLC-HRMS) and Fourier Transform Infrared Spectroscopy (FTIR) without isolation, and to evaluate cytotoxicity against WiDr cells. The research included ethanol extraction of P. serratifolia leaves, fractionation with n-hexane, ethyl acetate, and water, phytochemical, in vitro cytotoxicity assays, and FTIR and UHPLC-HRMS analyses. Phytochemical screening indicated the presence of flavonoids, tannins, saponins, and steroids. Aside from the ethanol extract, all three fractions showed moderate cytotoxic activity, with the ethyl acetate fraction (IC₅₀ = 49.12 μg/mL) selected for further analysis. FTIR spectra revealed functional groups including –OH, C–H, C=O, C=C, –CH₃, C–O, and =C–H. UHPLC-HRMS identified compounds such as luteolin, quercetin, apigenin, kaempferide, aurantioobtusin, isorhamnetin, scrofulein, and 5,7-dihydroxy-6-methoxy-3-phenyl-4H-chromen-4-one in the ethyl acetate fraction, with mass accuracy ranging from –0.53558 to 3.07641 ppm.